Near-infrared spectroscopy as an auxiliary tool in the study of child development - Suelen Rosa de Oliveira; Ana Carolina Cabral de Paula Machado; Débora Marques de Miranda; Flávio dos Santos Campos; Cristina Oliveira Ribeiro; Lívia de Castro Magalhães; Maria Cândida Ferrarez Bouzada (Sociedade de Pediatria de São Paulo, 2015)
OBJECTIVE: To investigate the applicability of Near-Infrared Spectroscopy (NIRS) for cortical hemodynamic assessment tool as an aid in the study of child development. DATA SOURCE: Search was conducted in the PubMed and Lilacs databases using the following keywords: ''psychomotor performance/child development/growth and development/neurodevelopment/spectroscopy/near-infrared'' and their equivalents in Portuguese and Spanish. The review was performed according to criteria established by Cochrane and search was limited to 2003 to 2013. English, Portuguese and Spanish were included in the search. DATA SYNTHESIS: Of the 484 articles, 19 were selected: 17 cross-sectional and two longitudinal studies, published in non-Brazilian journals. The analyzed articles were grouped in functional and non-functional studies of child development. Functional studies addressed the object processing, social skills development, language and cognitive development. Non-functional studies discussed the relationship between cerebral oxygen saturation and neurological outcomes, and the comparison between the cortical hemodynamic response of preterm and term newborns. CONCLUSIONS: NIRS has become an increasingly feasible alternative and a potentially useful technique for studying functional activity of the infant brain.